Expert guidance on prophylaxis and treatment of dermatologic adverse events with Tumor Treating Fields (TTFields) therapy in the thoracic region - Anadkat, Milan J.; Lacouture, Mario; Friedman, Adam; Horne, Zachary D.; Jung, Jae; Kaffenberger, Benjamin; Kalmadi, Sujith; Ovington, Liza; Kotecha, Rupesh; Abdullah, Huda Ismail; Grosso, Federica (Frontiers in Oncology, 2023)
Tumor Treating Fields (TTFields) are electric fields, delivered via wearable arrays placed on or near the tumor site, that exert physical forces to disrupt cellular processes critical for cancer cell viability and tumor progression. As a first-in-class treatment, TTFields therapy is approved for use in newly diagnosed glioblastoma, recurrent glioblastoma, and pleural mesothelioma. Additionally, TTFields therapy is being investigated in non-small cell lung cancer (NSCLC), brain metastases from NSCLC, pancreatic cancer, ovarian cancer, hepatocellular carcinoma, and gastric adenocarcinoma. Because TTFields therapy is well tolerated and delivery is locoregional, there is low risk of additive systemic adverse events (AEs) when used with other cancer treatment modalities. The most common AE associated with TTFields therapy is mild-to-moderate skin events, which can be treated with topical agents and may be managed without significant treatment interruptions. Currently, there are no guidelines for oncologists regarding the management of TTFields therapy-related skin AEs in the thoracic region, applicable for patients with pleural mesothelioma or NSCLC. This publication aims to provide guidance on preventing, minimizing, and managing dermatologic AEs in the thoracic region to help improve patient quality of life and reduce treatment interruptions that may impact outcomes with TTFields therapy.